Role of perceived stress in postoperative delirium: an investigation among elderly patients - Mukda Banjongrewadee (2020)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. Objectives: This study examined levels of perceived stress (PS), postoperative delirium (POD) and associated factors among Thai elderly patients undergoing elective noncardiac surgery. Background and aims: Preoperative PS and change after operation have not been widely studied. Moreover, psychological factors associated with PS and POD has been poorly investigated. Materials and Methods: In total, 429 elderly patients were recruited at a university hospital. The preoperative evaluation included sociodemographic data, health behaviors at risk, Perceived Stress Scale (PSS-10), Neuroticism Inventory (NI), Mental State Examination T10 (MSET10), Montreal Cognitive Assessment (MoCA) and Geriatric Depression Scale (GDS-15). Three-day postoperative evaluation included PSS-10 and Confusion Assessment Method Algorithm (CAM) or CAM-ICU for Delirium. Multiple regression and logistic regression analysis were performed to determine potential predictors. Results: Females were 58.97%, and the mean age was 69.93 ± 6.87 years. Mean pre- and postoperative PS were 12.77 ± 5.41 and 13.39 ± 5.26, respectively (P < 0.05). Multiple regression revealed that neuroticism, depression, and BMI predicted PS significantly. None of the independent variables was found to predict postoperative PS except for preoperative PS (p <.001). POD at the recovery room was predicted by preoperative PS (odds ratio = 1.181, 95% CI = 1.019–1.369), whereas overall POD was predicted by MoCA (odds ratio =.864, 95% CI =.771 -.968). Conclusion: Preoperative PS was significant in that it was associated with postoperative PS and POD. A careful assessment of preoperative PS as well as providing brief interventions for patients with high levels of this condition may reduce the risk of POD.